2012
DOI: 10.1007/s00441-012-1442-4
|View full text |Cite
|
Sign up to set email alerts
|

Traumatology of the optic nerve and contribution of crystallins to axonal regeneration

Abstract: Within a few decades, the repair of long neuronal pathways such as spinal cord tracts, the optic nerve or intracerebral tracts has gone from being strongly contested to being recognized as a potential clinical challenge. Cut axonal stumps within the optic nerve were originally thought to retract and become irreversibly necrotic within the injury zone. Optic nerve astrocytes were assumed to form a gliotic scar and remodelling of the extracellular matrix to result in a forbidden environment for re-growth of axon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 137 publications
0
12
0
Order By: Relevance
“…Other notable, strongly induced genes in Actn4 −/− podocytes included crystalline, gamma N (Crygn), a member of the crystallin superfamily that shows neurite-promoting properties through putative autocrine and paracrine effects (37, 38), the regulatory protein ‘growth arrest and DNA-damage-inducible 45 beta’ (Gadd45b), which has only recently been demonstrated to promote adult neurogenesis via epigenetic DNA demethylation (39), and toll-like receptor 4 (Tlr4), which has been suggested to directly associate the podocyte with the innate immune system to mediate glomerular injury in membranoproliferative glomerulonephritis (40) and which may offer a mechanistic link to the observed upregulation of Cxcl1 and other NF-κB-regulated genes. Among genes that were ≥2-fold downregulated in Actn4 −/− podocytes we identified e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Other notable, strongly induced genes in Actn4 −/− podocytes included crystalline, gamma N (Crygn), a member of the crystallin superfamily that shows neurite-promoting properties through putative autocrine and paracrine effects (37, 38), the regulatory protein ‘growth arrest and DNA-damage-inducible 45 beta’ (Gadd45b), which has only recently been demonstrated to promote adult neurogenesis via epigenetic DNA demethylation (39), and toll-like receptor 4 (Tlr4), which has been suggested to directly associate the podocyte with the innate immune system to mediate glomerular injury in membranoproliferative glomerulonephritis (40) and which may offer a mechanistic link to the observed upregulation of Cxcl1 and other NF-κB-regulated genes. Among genes that were ≥2-fold downregulated in Actn4 −/− podocytes we identified e.g.…”
Section: Resultsmentioning
confidence: 99%
“…They also showed that addition of exogenous β/γ-crystallins (1 mg injected intravitreally in the rat eye) activated retinal glial cells, stimulating astrocytes to secrete ciliary neurotrophic factor (CNTF) and up-regulating its downstream signaling pathway (JAK/STAT3). These studies, which have been recently reviewed by Thanos et al, (2012), suggest that β/γ-crystallins are able to alter the activity of signaling pathways by a mechanism, or mechanisms, yet to be identified.…”
Section: Expression Of β-Crystallins Outside Of the Lensmentioning
confidence: 99%
“…Indeed, crystallin mutations associated with cataract often lead to protein aggregation; however, little data has been reported for βB2-crystallin aggregation (Chen et al, 2013; Liu and Liang, 2005; Moreau and King, 2012a, b; Raju and Abraham, 2011). In addition, βB2-crystallin is also expressed in the retina and plays a key role in the protection of retinal neurons and the regeneration of their processes, critical aspects of the pathophysiology of glaucoma (Bohm et al, 2015; Prokosch et al, 2013; Thanos et al, 2012). …”
mentioning
confidence: 99%